Kajian Populasi Kepiting Kenari di Pulau Batudaka Kepulauan Togean, Sulawesi Tengah dan Rekomendasi Manajemen Populasi - Heryanto, Heryanto; Wowor, Daisy (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTThis study aimed to quantify the population of Birgus latro in the Batudaka di Togean islands, Central Sulawesi. The research on robber crab was conducted in Batudaka Island, Togean, Tomini Bay, Central Sulawesi. In the study site, 21 plots measuring of 50x50 m2 were created bounded by raffia. Feed in the form of shredded coconut is placed in each plot in the afternoon. At night was performed observations and catchs. In the "base camp" every crab crab carapace caught measured in carapace length and weight. During the study, 277 crabs were caught, consisted of 173 males (62.45%) and 104 (37.55%) females. Based on the formula calculation of Schiller (1992) population figures obtained 821 803 Â± 195 030 crabs in Batudaka Island. By regression analysis between carapace length with weight, it was found that the growth of B. latro is negative allometric, i.e., weight gain is faster than the increase length of carapace. The weight gain of female is slightly higher than that of the male. Whether male crab population or female equally composed of 9 age groups. This study showed that 66.7% of male crab and 29.1% of female crab has entered the market size.Keywords: Birgus, crab, carapace